Finnmarksloven er vedtatt. Om de vesentligste endringene i loven i forhold til regjeringens lovforslag i Ot.prp. nr 53 (2002-2003) - Ravna, Øyvind (Fagbokforlaget, 2005)
The Finnmark Act was recently approved in the parliament by a clear majority. A half-century discussion concerning land rights of the Saami people has culminated in an Act concerning the «right to land and water» in Finnmark County. The legislative history of the Act covers approximately 25 years, and started when the Saami Law committee was appointed in autumn 1980. In this paper the author examines this legislative history, emphasizing the main changes in the adopted act in relation the disputed bill to the parliament in spring 2003 (Ot.prp. nr. 53 (2002-2003). Pursuant to the Act, a land commission and special tribunal will be established that will clarify and settle land rights questions. The author observes that the land consolidation court, as proposed by the Saami Law committee, is not given any place in the Act. Finally, the author remarks that the changes from the bill of 2003, up to the adoption of the Act in June this year, have led to an act which is a major step forward in giving the people in Finnmark County rights to their natural resources and common land. The Act also represents strong support for the land rights of the Saami people.